Korelasi Tingkat Pengetahuan denngan Perilaku Swamedikasi Obat Analgesik di Masyarakat Semper Barat, Jakarta Utara - Zainul Islam; Endang Sulistyaningsih; Fanni Luthfianti (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2025)
Self-medication is a person's action in determining and using medicine independently to treat a disease or its symptoms. The benefits of this practice include cost efficiency and helping to ease the burden of health services. However, there are risks if done without adequate knowledge; it can cause side effects or additional costs. Good knowledge greatly supports correct self-medication behavior in the community. The type of drug that is often used during self-medication is analgesics, which function to suppress pain. This study aims to analyze the correlation between the level of knowledge and self-medication behaviour in the use of analgesic drugs in the community in Semper Barat Village, North Jakarta. The research design used a quantitative approach with an instrument in the form of a questionnaire that had passed validity and reliability tests. Four hundred respondents from 9 RW in Semper Barat Village participated in this study. Data were processed through Chi-square and Spearman-rho analysis. The research data showed that the majority of respondents had a sufficient level of knowledge (64.3%) and behaved sufficiently (52.5%). In the chi-square analysis, except for education, most characteristics did not correlate significantly with knowledge or behaviour. The results of the Spearman-rho test showed a significant correlation (p = 0.011) between knowledge and analgesic self-medication behaviour.